Studi Konseptual Pengembangan Media Interaktif PowerPoint untuk Pembelajaran IPA Materi Perubahan Wujud Benda di Kelas IV MI Kasyiful Ulum Jember - Asiatul Hafsoh; Muhammad Suwignyo Prayogo; Hani’ Amari’a; Mirna Majidatul Maghfiroh (Universitas Palangka Raya, 2025)
This research is a conceptual study that focuses on the design of PowerPoint-based interactive media to support Natural Science (IPA) learning on the material of changes in the state of matter in grade IV MI Kasyiful Ulum Jember. This interactive media is designed to create an interesting and effective learning experience through visualization, animation, and interactive exercises, which are expected to improve students' conceptual understanding. The research approach is carried out through a literature review and theoretical analysis of various references related to digital learning design, constructivism theory, and previous research results. The final product of this research is a conceptual design of PowerPoint media designed to be used by teachers in basic science learning. This research does not involve field data collection, but aims to provide a conceptual basis for further research on the development of learning media. It is hoped that this interactive media can be an effective tool in improving the quality of science learning at the elementary school level, especially on the material of changes in the state of matter.